2022
DOI: 10.1002/hyp.14479
|View full text |Cite
|
Sign up to set email alerts
|

Untangling harvest‐streamflow responses in foothills conifer forests: Nexus of teleconnections, summer‐dominated precipitation, and storage

Abstract: This study re‐evaluated data from the historical Tri‐Creeks Experimental Watershed (1967–1988) in Alberta, Canada to address the initial question of forest harvest effects on streamflow and investigate the potential influence of teleconnections, summer‐dominated precipitation, and watershed storage on runoff generation. Tri‐Creeks has deep (up to 21 m) glacial deposits underlain by folded and faulted sedimentary bedrock with considerable potential for subsurface water storage. Timing of the conifer forest harv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…Although runoff efficiencies are generally greater following snowmelt, in contrast to snow‐dominated regions, the overall contribution of snowmelt to annual R is low in the study catchments (Redding & Devito, 2010). Accumulation of snow water equivalent (CMw median = 120 mm) is low relative to potential soil and depression S (Redding & Devito, 2011), and there may also be considerable loss to groundwater recharge (Smerdon et al., 2008) resulting in minor snowmelt peaks in annual hydrographs in most years for BP catchments, as observed in summer P ‐dominated montane catchments (Goodbrand et al., 2022). Cyclonic summer patterns across the BP result in considerable range in magnitude, timing, and spacing of rain events, leading to dynamic antecedent moisture conditions that are synchronized with maximum rates of catchment ET (Devito et al., 2005; Mwale et al., 2011; Wells et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Although runoff efficiencies are generally greater following snowmelt, in contrast to snow‐dominated regions, the overall contribution of snowmelt to annual R is low in the study catchments (Redding & Devito, 2010). Accumulation of snow water equivalent (CMw median = 120 mm) is low relative to potential soil and depression S (Redding & Devito, 2011), and there may also be considerable loss to groundwater recharge (Smerdon et al., 2008) resulting in minor snowmelt peaks in annual hydrographs in most years for BP catchments, as observed in summer P ‐dominated montane catchments (Goodbrand et al., 2022). Cyclonic summer patterns across the BP result in considerable range in magnitude, timing, and spacing of rain events, leading to dynamic antecedent moisture conditions that are synchronized with maximum rates of catchment ET (Devito et al., 2005; Mwale et al., 2011; Wells et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Because of the modification of the wind as it rises above the mountains, the descending wind on the lee side of the Rockies have high velocities, high temperatures, and high humidity deficits, which enables the wind to rapidly modify local h, H, and Ts and consequently modify local Tair (Equation ). A well‐known example of this orographic effect on wind is the Chinook wind that modifies water and heat energy fluxes in the valleys and plains on the lee side of the Rockies (Beran, 1967; Burrows, 1903; Goodbrand et al, 2022; MacDonald et al, 2018; Oard, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Another local source of horizontal temperature gradient that drive modification of T air (Equation 3) in the MRB is the local changes in T s and advected H owing to heterogenous land cover, such as snow cover, water surfaces, and irrigated surfaces (Harder et al, 2019;Neumann & Marsh, 1998;Philip, 1959;Schlögl et al, 2018). These land cover types account for a large proportion of the MRB land surface area during the year (Gleick, 1989;Mehta et al, 2013;Wise et al, 2018) and they undergo large thermal changes during the year, for example, snow accumulation/thaw, growing/fallow season, and frozen/unfrozen water surfaces.…”
Section: F I G U R E 11mentioning
confidence: 99%
“…Others have found that land use and LC had little impact on GWR simulation, or that land use and LC impacts were smaller than those of climate change (Guerrero‐Morales et al, 2020; Mohan et al, 2018; Morgan et al, 2021; Shuler et al, 2021). These differences are most likely due to the fact that it can be challenging to distinguish the impacts of climate change from the impacts of land use and LC changes on GWR, and on all components of the water budget more generally (Assani et al, 2021; Goodbrand et al, 2022; Young et al, 2019). The study scale could also determine the importance of the impacts of land use and LC changes on GWR simulations, as local impacts of changes are not necessarily visible at larger scales (Shuler et al, 2021; Zomlot et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly,Assani et al (2021) andGoodbrand et al (2022) identified average slope and soil water storage as countering the impact of agricultural development on forested land and wood harvesting on the river flow of six watersheds of different sizes in southern Quebec (Canada) and three headwater watersheds in Alberta (Canada). While an increase in fall and spring rainfall was the second reason identified byAssani et al (2021) for the increase in minimum flow during these seasons in southern Quebec,Goodbrand et al (2022) found that climate variability also reduced impacts of land-use changes on river flow. Similarly, moister future conditions expected in southern Quebec counter balanced the decrease in GWR rates simulated using HB LC due to afforestation taking place on lowpermeability surficial deposits, thus reducing the impact of LC changes on GWR (Figure6).…”
mentioning
confidence: 99%